Long Non-Coding RNA H19 Positively Associates With Aspirin Resistance in the Patients of Cerebral Ischemic Stroke - Wang, Jue; Cao, Bin; Gao, Yan; Han, Dong; Zhao, Haiping; Chen, Yuhua; Luo, Yumin; Feng, Juan; Guo, Yanxia (Frontiers in Pharmacology, 2020)
Background and purpose: Aspirin is a novel anti-platelet drug that is intensively recommended for the prevention and treatment of cerebral ischemic stroke. However, the existence of aspirin resistance weakens the effects of aspirin and usually induces the recurrence of ischemic stroke. While the mechanism underlying aspirin resistance is still unclear. Long non-coding RNA H19 (H19) is closely associated with the onset and prognosis of cerebral ischemic stroke. Since the relationship between H19 and aspirin resistance have never been reported, herein, we aimed to evaluate the H19 expression in aspirin-resistant ischemic stroke patients and subsequently, ascertain the ability of H19 to diagnose aspirin resistance. Methods: We included 150 patients with acute cerebral ischemic stroke who were followed up for one year to determine stroke recurrence. Levels of 11-dehydro thromboxane B2 (11dhTXB2) in urine were tested to evaluate the status of aspirin resistance, and those of H19 and 8-iso-prostaglandin-2α in plasma were assessed. The relationship between 11dhTXB2 or and 8-iso-prostaglandin-2α and H19, and the receiver operating characteristic curve of H19, the association of H19 and aspirin resistance with the recurrence of stoke were statistically analyzed. Results: Plasma H19 was significantly up-regulated in patients with aspirin resistance (p=0.0203), and the H19 levels were positively associated with urine 11dhTXB2/creatinine (R=0.04364, p=0.0106) and positively associated with the level of 8-iso-PGF2α (R=0.04561, p=0.0089). The ROC curves indicated that H19 can sensitively and specifically diagnose aspirin resistance (area under the curve, 0.8005; 95%CI, 0.7301-0.8710; p < 0.0001; specificity, 75.86207%; sensitivity, 73.84615%.). H19 is an independent risk factor for aspirin resistance (OR=1.129, p=0.0321), and aspirin resistance and H19 are closely related with ischemic stroke recurrence. Conclusions: H19 is closely associated with aspirin resistance, and H19 probably induces aspirin resistance through increasing the production of 8-iso-prostaglandin-2α. Besides which, H19 may serve as a serological marker for diagnosing aspirin resistance with high specificity and sensitivity, and the test of H19 could give clues to the recurrence of ischemic stroke.